Comparative Study of Attenuation of effects of Intubation on Blood Pressure Using IV Xylocard and IV Beta Blocker (Esmolol) - Mirza Afzal Baig (Academia Anesthesiologica International, 2019)
Background: The occurrence of cardio vascular reactions to laryngoscopy and tracheal intubation has attracted the attention of anaesthesiologists and methods to avoid these potentially harmful responses even though transitory have been sought, particularly in critically ill patients, hypertensive patients. Tracheal intubation under light general anaesthesia is consistently accompanied by a pressor response, tachycardia and in some instances by cardiac arrhythmias. This pressor response, which was recognised early as 1951 is due to sympathetic reflex provoked by stimulation of the epipharynx and laryngopharynx. Subjects and Methods: Seventy five (75) patients belonging to ASA grade 1 & 2 scheduled for general surgical, orthopaedic surgical, ENT, gynocological surgical producers were studied. Results: The age of the patients varied from 10 to 60 years. The MAP in group A decreased after induction. There was a highly significant raise to 109+/-11 mm Hg during laryngoscopy and intubation. This decreased to 105+/-9mm Hg after five minutes which is not significant. Conclusion: These responses are transitory, variable and are much more marked in a hypertensive patient than in the normotensive patient. Once the laryngoscopy and endotracheal intubation is completed, the increase in pulse and blood pressure subside, but the dysrhythmia persists for more than 2-3 minutes.